Adapting Existing Practices For ISMS-Certified Organizations in Support of Responsible AI - David Lau Keat Jin; Ganthan Narayana Samy; Fiza Abdul Rahim; Mahiswaran Selvananthan; Nurazean Maarop; Mugilraj Radha Krishnan; Sundresan Perumal (Penerbit UTM Press, 2026)
Indexed by ERA